111 POST-OPERATIVE OUTCOME OF ADULT PATIENTS WITH PRE-TRICUSPID SHUNT UNDERGOING DEFECT CLOSURE. (15th December 2022) - Magnani, Ilenia; Manes, Alessandra; Dardi, Fabio; D´angelo, Emanuela Concetta; Guarino, Daniele; Ballerini, Alberto; Rotunno, Mariangela; Donato, Federico; Bertozzi, Riccardo; Martini, Giulia; Palazzini, Massimiliano; Donti, Andrea; et al.
Abstract: Background: patients with pulmonary arterial hypertension (PAH) associated with corrected congenital heart disease (CHD) have a worse prognosis than other 3 groups of patients with PAH associated with CHD (Eisenmenger, small defect, prevalent systemic-to-pulmonary shunt). For this reason, in CHD the indication and timing of defect repair should be evaluated carefully. Current recommendations rely essentially on pulmonary vascular resistance (PVR) when deciding about defect closure, but this may be insufficient as PAH may develop even in cases of normal pre-operative PVR. In particular, patients with PVR below 3 WU are usually deemed operable and patients between 3 and 5 WU (gray zone) are deemed operable in case of significant persistence of left-to-right shunt. Detecting preoperative characteristics of patients who developed PAH after pre-tricuspid shunt repair can be helpful when deciding about CHD correction. Methods: we enrolled adult patients referred to our centre for the suspicious of PAH after pre-tricuspid shunt correction from 2006 to 2021. We evaluated clinical, echocardiographic and hemodynamic parameters before and after defect repair (a post-correction hemodynamic evaluation was performed only in case of non-invasive signs of PAH) and PAH after defect closure was defined by the concomitant occurrence of a mean pulmonary artery pressure (mPAP) >25 mmHg and PVR >3 WU. Continuous variables were summarized using mean and standard deviation and Student's t-test was used for comparisons. Results: sixty patients were included in the final analysis. After shunt repair, 10 patients (16.6%) were diagnosed with PAH during the long-term follow-up, with no differences given by the type of defect or type of correction. As expected, these patients already had an abnormal baseline hemodynamic profile: 7 had a clear PAH diagnosis before the correction [mPAP >25 mmHg with PVR between 3 and 5 WU and with a pulmonary/systemic cardiac output ratio of at least 1.5] while 3 had pulmonary hypertension related to high pulmonary blood flow (mPAP >25 mmHg and PVR <3 WU). At the baseline hemodynamic evaluation, patients with PAH after shunt repair had higher mPAP (39±6 vs 24±10 mmHg, p <0.001) and PVR (3.7±1.2 vs 1.5±0.9, p <0.001) and lower mixed venous oxygen saturation (81±3 vs 87±3, p <0.001). At the baseline echocardiographic evaluation, patients with PAH after shunt repair had a greater right ventricular hypertrophy (RV wall thickness 0.7±0.1 vs 0.5±0.2 cm, p= 0.011), tricuspid regurgitation jet velocity (424±63 vs 319±62 cm/s, p <0.001) and a significant lower RV fractional area change (34±8 vs 43±9%, p= 0.009). Conclusions: currently there are no established evidence-based algorithms to predict the development of PAH after defect correction. Our study shows that this condition may persist or develop even when PVR values are lower than 5 WU despite a significant left-to-right shunt before defect closure. Patients with grey zone PVR values require a global clinical, instrumental and hemodynamic assessment that takes into account more than bare calculated PVR that, especially in patients with a high pulmonary blood flow, can be less reliable.